A consequence of immature breathing induces persistent changes in hippocampal synaptic plasticity and behavior: a role of prooxidant state and NMDA receptor imbalance - Arias-Cavieres, Alejandra; Garcia, Alfredo J. (Frontiers in Molecular Neuroscience, 2023)
Underdeveloped breathing results from premature birth and causes intermittent hypoxia during the early neonatal period. Neonatal intermittent hypoxia (nIH) is a condition linked to the increased risk of neurocognitive deficit later in life. However, the mechanistic basis of nIH-induced changes to neurophysiology remain poorly resolved. We investigated the impact of nIH on hippocampal synaptic plasticity and NMDA receptor (NMDAr) expression in neonatal mice. Our findings indicate that nIH induces a pro-oxidant state, that leads to an imbalance in NMDAr subunit composition favoring GluN2B over GluN2A expression and impairs synaptic plasticity. These consequences persist in adulthood and coincide with deficits in spatial memory. Treatment with the antioxidant, manganese(III) tetrakis(1-methyl-4-pyridyl)porphyrin (MnTMPyP), during nIH effectively mitigated both immediate and long-term effects of nIH. However, MnTMPyP treatment post-nIH did not prevent the long-lasting changes in either synaptic plasticity or behavior. In addition to demonstrating that the pro-oxidant state has a central role in nIH-mediated neurophysiological and behavioral deficits, our results also suggest that targeting the pro-oxidant state during a discrete therapeutic window may provide a potential avenue for mitigating long-term neurophysiological and behavioral outcomes that result from unstable breathing during early postnatal life.